Analisis Penggunaan Sufiks Bahasa madura dalam Karya Cerpen pada Santri Fathul Mu'ien Panti Jember - Jasmin Fauzia; M. Toyyib Mustofa Lathif; Laila Nurmayanti; Hasan Suaedi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study analyzes the use of Madurese suffixes in short stories written by students of Pondok Pesantren Fathul Mu'ien, Jember. The research focuses on the application of seven types of Madurese suffixes, namely {-e}, {-a}, {-an}, {-en}, {-na}, {-ana}, and {-aghi}, within verbs, nouns, and adjectives. A descriptive qualitative method with a morphological analysis approach was employed. Data were collected through documentation of the students' short story works. The results show that Madurese suffixes contribute unique morphophonemic nuances, such as emphasis, possession, and action indication. Furthermore, the use of suffixes reflects the students' creativity in utilizing the Madurese language as a medium of literary expression. These findings emphasize the significant role of morphology in preserving cultural heritage and enriching Indonesia's linguistic studies. This research is expected to serve as a reference in linguistic and regional literature studies, particularly regarding the development of the Madurese language in contemporary literary works.